Is neoadjuvant chemoradiotherapy always necessary for mid/high local advanced rectal cancer: A comparative analysis after propensity score matching. Issue 8 (August 2017) - Zhang, Y.; Sun, Y.; Xu, Z.; Chi, P.; Lu, X.
Abstract: Aim: This study was aimed to compare perioperative and oncological outcomes of mid/high locally advanced midrectal cancer (LARC) treated with neoadjuvant chemoradiotherapy (NCRT) vs. surgery alone, and to identify risk factors for local recurrence in mid/high LARC. Method: A total of 471 mid/high LARC patients treated with surgery alone or NCRT (50.4 Gy in 28 fractions) with concurrent FOLFOX/XELOX followed by TME in 6–8 weeks from 2008 to 2014 were matched 1:1 by using propensity score analysis. Perioperative and survival outcome was compared between groups. Multivariate analyze was performed to identify risk factors for local recurrence. Results: Two hundred and two patients were matched for the analysis. Postoperative morbidity was similar between groups. With a mean follow-up of 57 months, the 5-year overall survival (NCRT vs. surgery alone: 80.4% vs. 81.4%; p  = 0.978), 5-year local recurrence rates (3.1% vs. 5%; p  = 0.467), and 5-year distant metastasis rates (29.5% vs. 23.7%; p  = 0.140) were similar between two groups. Cox regression analysis showed that the circumferential resection margin (CRM) involvement (OR = 5.205, p  = 0.005) was the only risk factor for local recurrence in mid/high LARC patients. Conclusion: In matched cohorts of mid/high LARC patients, surgery alone provided comparable oncological outcome, when compared with NCRT. CRM involvement was the only risk factor for local recurrence in mid/high rectal cancer. NCRT may not be always needed in mid/high LARC. A threatened CRM could be diagnosed up front and prevented by selecting CRT for these patients.